2020
DOI: 10.20869/auditf/2020/160/030
|View full text |Cite
|
Sign up to set email alerts
|

The Content Analysis of Reporting on Sustainable Development Goals

Abstract: The epitome of sustainable development resides in the process of transformation through which resource exploitation, investment direction, technological development orientation, and institutional changes are in harmony and lead to the enhancement of the potential to meet present and future human needs and aspirations, based on the motto “Leaving no one behind” (UN, 2015). This is materialised into the 2030 Agenda for Sustainable Development, “Transforming Our World”, defined by 17 Sustainable Development Goals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Thus, all public reports of the companies available on their official websites were screened in full and reviewed [75,82], in order to identify the sustainable development goals that they are addressing, as well as the qualitative and quantitative targets, efforts, or measurements for each SDG [56,78]. By applying search queries for the occurrence of key words, such as "sustainable," "sustainability," "SDG," the textual analysis [75,76] was conducted in order to determine whether the sampled companies addressed the SDGs in their reports.…”
Section: Methods Used For the Assessment Of The Quality Sdg Score Based On A Content Analysis Approachmentioning
confidence: 99%
“…Thus, all public reports of the companies available on their official websites were screened in full and reviewed [75,82], in order to identify the sustainable development goals that they are addressing, as well as the qualitative and quantitative targets, efforts, or measurements for each SDG [56,78]. By applying search queries for the occurrence of key words, such as "sustainable," "sustainability," "SDG," the textual analysis [75,76] was conducted in order to determine whether the sampled companies addressed the SDGs in their reports.…”
Section: Methods Used For the Assessment Of The Quality Sdg Score Based On A Content Analysis Approachmentioning
confidence: 99%
“…The interest in carrying out studies regarding non-financial reporting and sustainability indicators of Romanian companies has registered an increasing trend lately. Thus, several studies have been conducted on listed companies during the last decade [2,4,47,64,78] and have shown great progress in obtaining a high level of environmental, social, and governance performance. The tendency of these companies to publish sustainability reports is increasing [2].…”
Section: Background On Non-financial Disclosure and Hypothesis Developmentmentioning
confidence: 99%
“…Studies [79][80][81][82] that have analyzed non-financial reporting practices in correlation with the activity sector observed that some sectors differ in the level of sustainability disclosure. From the cross-sectional analysis by industries conducted on sampled Romanian companies, in the period 2017-2019, Nechita et al [4] emphasizes the similarities and reporting differences influenced by the industrial branches. Hurghiş [1] shows that those companies operating in the financial field tend to present more information than companies in the health field.…”
Section: Background On Non-financial Disclosure and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations